Citizen science-based jellyfish observation initiatives in the Mediterranean Sea - Dor Edelist; Antonio Canepa-Oneto; Joel Azzopardi; Ainara Ballesteros; Jesús Bellido; Ferdinando Boero; Cesar Bordehore; Alan Deidun; Eva S. Fonfría; Adam Gauci; Josep Maria Gili; Sonia K. M. Gueroun; et al. (Hydrobiologia, 2025)
We present Citizen Science-based Jellyfish Observation Initiatives (CS JOIs) across the Mediterranean Basin and propose a path toward standardization of the data they produce. We explored data collection and management through a shared database schema. Using an expert opinion questionnaire and adhering to standards that are recognized globally (e.g., by GBIF, OBIS, and EMODnet) such as Darwin Core and IOOS terminology, we propose a three-stage approach toward data management and standardization. JOIs vary in purpose, function, language, data collection, validation methodology, outreach, and levels of citizen engagement and training. This diversity presents unique opportunities and challenges for data collection and management. JOIs typically combine the dual role of providing real-time alert systems and enhancing our long-term knowledge of jellyfish distribution and, eventually, ecology. When global reporting systems are considered, local initiative identity, language, purpose, and community must be preserved to allow meaningful CS processes to evolve, while the integration of JOIs within them (and data collection and management in general) must be performed via standardized and shared methodologies. Finally, we discuss the contribution of novel technologies toward improving the activities and management of JOIs worldwide.